Study of Weathering Effect, and the Solution on the Diffusion Coefficient of the PET, Mineral Water, and Al-Badawi Vinegar Bottles samples - H, Nahida J (Al-Nahrain Journal of Science, 2012)
The aim of this work is to study the absorptive properties of PET, and bottle material samples for mineral water and black and white Al-Badawi vinegar (acidic acid (CH3COOH)). PET samples were prepared by extrusion method, and take the bottle samples from the bottles, which are used as a container to save it. The fundamental reason for the permeability of polymers is their relatively high level of molecular motion. Since two different solutions were used to evaluate the diffusion behavior of specimens. By using mineral water for two kinds of specimen (PET, and samples of the bottle material at three conditions ((1)-indoor,(2)- in refrigerator, and(3)-outdoor) to study the weathering effect on polymer absorptive involved. It was found that PET-3(out door) was the most water absorbing polymer. It was attributed to free radical induced by the photo degradation, and the PET-2, and bottle samples (2-in refrigerator) were the lowest, which attributed to the thermal and photo degradation for the out door condition, whereas the lowest for the samples(2-in refrigerator). It was attributed to the freezing free radical in polymer of the lowest effect, so the weight gain will be the lowest. The diffusion coefficient of the bottle samples (2-in refrigerator) was of the lowest value (previous reasons), and also attributed to the bottle sample material (PET+ Additives (as stabilizers)), which caused in decreasing in thermal, and photo degradation effects.By using acidic acid at different concentration (4.6%, 6.4, and 100% of CH3COOH)) as black, and white Al-badawi vinegar, and pure acidic acid. It was found increasing in absorptive with increasing of CH3COOH concentration, so the best absorptive for the highest concentration (100%) for two samples (PET, and bottle samples). CH3COOH had a deterioration effect. This effect had led to formation of voids and gaps, beside the ones originated in the specimens during manufacturing and processing stages, and these gaps would be filled with the solutions, leading to an increase in weight. It was concluded that the diffusion coefficient was very low for all samples and in all solutions of order less than 10-14m2/sec , so it was recommended to use PET for manufacturing the bottle(container) to save the solutions(water, and acidic solution, because it was a good barrier for solutions.